Localization of a Bose-Fermi mixture in a bichromatic optical lattice - Cheng, Yongshan [UNESP]; Adhikari, Sadhan Kumar [UNESP] (Amer Physical Soc, 2011)
We study the localization of a cigar-shaped superfluid Bose-Fermi mixture in a quasiperiodic bichromatic optical lattice (OL) for interspecies attraction and intraspecies repulsion. The mixture is described by the Gross-Pitaevskii equation for the bosons, coupled to a hydrodynamic mean-field equation for fermions at unitarity. We confirm the existence of the symbiotic localized states in the Bose-Fermi mixture and Anderson localization of the Bose component in the interacting Bose-Fermi mixture on a bichromatic OL. The phase diagram in boson and fermion numbers showing the regions of the symbiotic and Anderson localization of the Bose component is presented. Finally, the stability of symbiotic and Anderson localized states is established under small perturbations.